A multicenter cross-sectional study in infants with congenital heart defects demonstrates high diagnostic yield of genetic testing but variable evaluation practices - Matthew D. Durbin; Lindsey R. Helvaty; Ming Li; William Border; Sara Fitzgerald-Butt; Vidu Garg; Gabrielle C. Geddes; Benjamin M. Helm; Seema R. Lalani; Kim L. McBride; Alexis McEntire; Dana K. Mitchell; et al. (Genetics in Medicine Open, 2023)
Purpose: For patients with congenital heart disease (CHD), the most common birth defect, genetic evaluation is not universally accepted, and current practices are anecdotal. Here, we analyzed genetic evaluation practices across centers, determined diagnostic yield of testing, and identified phenotypic features associated with abnormal results. Methods: This is a multicenter cross-sectional study of 5 large children’s hospitals, including 2899 children ≤14 months undergoing surgical repair for CHD from 2013 to 2016, followed by multivariate logistics regression analysis. Results: Genetic testing occurred in 1607 of 2899 patients (55%). Testing rates differed highly between institutions (42%-78%, P < .001). Choice of testing modality also differed across institutions (ie, chromosomal microarray, 26%-67%, P < .001). Genetic testing was abnormal in 702 of 1607 patients (44%), and no major phenotypic feature drove diagnostic yield. Only 849 patients were seen by geneticists (29%), ranging across centers (15%-52%, P < .001). Geneticist consultation associated with increased genetic testing yield (odds ratio: 5.7, 95% CI 4.33-7.58, P < .001). Conclusion: Genetics evaluation in CHD is diagnostically important but underused and highly variable, with high diagnostic rates across patient types, including in infants with presumed isolated CHD. These findings support recommendations for comprehensive testing and standardization of care.